Green criminology : crime, justice, and the environment - Lynch, Michael J.; Long, Michael A.; Stretesky, Paul; Barrett, Kimberly L. (University of California Press, 2017)
"This book provides an overview and assessment of green criminology. Based on a political-economic analysis, Green Criminology draws attention to the ways in which the political-economic organization of capitalism causes ecological destruction and disorganization. Focusing on real-world impact, chapters include political-economic examinations of ecological withdrawals, ecological additions, toxic towns, wildlife poaching and trafficking, environmental justice, environmental laws, and nongovernment environmental organizations. The book also explores how ecological footprint, planetary boundary analysis, and other scientific research applies to green criminological analysis"--Provided by publisher.